Interpersonal Violence Among Heterosexual and Sexual Minority Youth: Descriptive Findings From the 2017 Youth Risk Behavior Surveillance System - Levine, Ethan C. (Journal of interpersonal violence, 2022)
Interpersonal violence is pervasive among youth in the United States. Sexual minority youth are disproportionately impacted. Utilizing data from the 2017 Youth Risk Behavior Surveillance System (YRBS, N = 12,868), this study describes the disparities in victimization among heterosexual and sexual minority youth. Sexual minority status was operationalized to include nonheterosexual identity (e.g., bisexual) and/or behavior (e.g., reporting same- and different-sex partners). Other predictors included sex (male/female), a sexuality*sex interaction term, age, and race/ethnicity. Outcomes included lifetime forced sexual intercourse and 12-month incidence of sexual violence, physical violence in relationships, sexual violence in relationships, in-school bullying, and cyberbullying. Approximately 15% (n = 1,974) of participants were classified as sexual minority youth and 48% (n = 6,213) self-identified as female. More than half (56%, n = 7,190) identified as racial and/or ethnic minorities. In bivariate logistic regression, sexual minority youth were significantly more likely to report all outcomes (p < .001). In multivariable logistic regression, sexual minority and female youth were significantly more likely to report all outcomes (p < .001). With the exception of physical violence in dating, sexuality*sex interaction terms were significant predictors for all outcomes (p < .001), indicating that the risks associated with sexual minority status are heightened for male youth. This study concludes with a call for more attention toward violence among and against sexual minority youth. Although some prevention and response efforts address the unique needs and experiences of these youth, particularly antibullying initiatives, efforts to address sexual and dating violence often emphasize heterosexual contexts and communities.